Transforming Mosque Management: Adopting Jogokariyan Best Practices to Enhance Al Hidayah Taklim Council's Recitation Programs - Muhamad Subhi Apriantoro; Sahara , Safira; Putri , Kiky Alviana; Hidayat, Syamsul (Global Research Network, 2024)
Mosques function more than just places of worship in Islam; they are educational, social, and economic centers that play a vital role in community development. The Al Hidayah Taklim Council faces challenges in managing its activities effectively, especially in terms of empowerment and management. This comparative study explores the best practices of the Jogokariyan Mosque in Yogyakarta, known for its innovations in the Rice ATM program and the Da'wah Map. The Rice ATM program focuses on providing food needs respectably and sustainably, while the Da'wah Map optimizes da'wah activities through area mapping, pilgrim data collection, and structured planning. This study highlights the critical role of women in both programs, from collecting donations to organizing activities. By adopting best practices from the Jogokariyan Mosque, it is hoped that the Al Hidayah Taklim Council can increase the effectiveness of management, strengthen the empowerment of the ministry, and improve the sustainability of the study program. This initiative aims to enhance study management, increase congregation participation, and build a more solid and sustainable community